Termination of atrial fibrillation during pharmacological cardioversion in the goat requires inter-atrial synchronisation of conduction. (24th May 2021) - Sobota, V; Van Hunnik, A; Zeemering, S; Gatta, G; Opacic, D; Scaf, B; D"alessandro, E; Oyaert, K; Diness, JG; Sorensen, US; Van Der Heyden, M A G; Schotten, U; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): ITN Networks PersonalizeAF: Personalized Therapies for Atrial Fibrillation. A Translational Approach, No. 860974; CATCH ME: Characterizing Atrial fibrillation by Translating its Causes into Health Modifiers in the Elderly, No. 633196; MAESTRIA: Machine Learning and Artificial Intelligence for Early Detection of Stroke and Atrial Fibrillation, No. 965286; AFib-TrainNet: EU Training Network on Novel Targets and Methods in Atrial Fibrillation, No. 675351 Netherlands Heart Foundation: CVON2014-09, RACE V Reappraisal of Atrial Fibrillation: Interaction between hyperCoagulability, Electrical remodeling, and Vascular Destabilization in the Progression of Atrial Fibrillation Background Few studies report on mechanisms leading to termination of atrial fibrillation (AF). Purpose To characterise electrophysiological parameters and conduction patterns during the transition from AF to sinus rhythm under various conditions of AF termination. Methods A retrospective evaluation of 6 goat studies was performed. AF was maintained for 3-4 weeks in 29 animals. Four animals were in SR. Unipolar electrograms were acquired with one 249-electrode array/atrium. Pharmacological termination of AF was evoked by various drugs; AP14145 (n = 5), PA6 (n = 7), XAF-1407 (n = 9) vernakalant (n = 8). In animals with sinus rhythm, AF was acutely induced and terminated spontaneously. Baseline AF and ≤3 recordings of the last 10 seconds preceding AF termination were analysed. Intervals with temporal continuous and periodic activity were distinguished in the recordings. AF cycle length (AFCL), conduction velocity and path length were determined for each interval. Results In total, 85 AF terminations were recorded. Switches between temporal continuous and periodic activity were seen frequently during AF. However, termination of AF was always preceded by a phase of periodic activity (PA). The final phase of PA persisted for a median number of 21 [IQR 10-28] cycles in the left atrium and somewhat shorter in the right atrium, Table 1. This final phase of PA was accompanied by a profound bi-atrial increase of AFCL, conduction velocity and path length and a disappearance of inter-atrial cycle length differences. Equipotent changes were not observed in the preceding PAs. During the final AF beats, the number of wave fronts were low, 1 or 2. Interestingly, 92% of the patterns during the last beats of AF involved the Bachmann's bundle as main source of atrial conduction. Conclusion AF termination is preceded by an increased organisation of fibrillatory conduction, associated with abrupt prolongation of the path length. Propagation in atrial free walls regularly originated from the Bachmann's bundle. These findings suggest that AF termination was not a random process but follows common spatiotemporal patterns.